Living Together, Living Apart : Rethinking Jewish-Christian Relations in the Middle Ages - Elukin, Jonathan M., 1961- (Book collections on Project MUSE., 2007)
This book challenges the standard conception of the Middle Ages as a time of persecution for Jews. Jonathan Elukin traces the experience of Jews in Europe from late antiquity through the Renaissance and Reformation, revealing how the pluralism of medieval society allowed Jews to feel part of their local communities despite recurrent expressions of hatred against them. Elukin shows that Jews and Christians coexisted more or less peacefully for much of the Middle Ages, and that the violence directed at Jews was largely isolated and did not undermine their participation in the daily rhythms of Eu.